A comparison of three tests for rubella antibody screening. Issue 6 (June 1979) - Morgan-Capner, P; Pullen, H J; Pattison, J R; Bidwell, D E; Bartlett, A; Voller, A
Abstract : Sera from 1000 women attending antenatal clinics were screened for the presence of rubella antibody by haemagglutination inhibition (HI), single radial haemolysis (SRH), and enzyme-linked immunosorbent assay (ELISA). With 925 sera concordant results were obtained with all three tests. There were 46 false-negative HI tests due to the necessity of allowing for residual non-specific inhibitors. With SRH there was one false positive and three that were negative by SRH but HI- and ELISA-positive. By ELISA 14 sera gave a false-positive result (OD 405 nm greater than or equal to 0.2). Ten of these could be eliminated by taking an OD 405 nm of 0.5 as the threshold but then another 10 sera became false negatives.